Record high magnetic exchange and magnetization blockade in Ln2@C79N (Ln = Gd(III) and Dy(III)) molecules: a theoretical perspective - Singh, Mukesh Kumar; Yadav, Neeraj; Rajaraman, Gopalan (Chemical communications (Cambridge, England), 2015)
Ab initio and DFT calculations reveal a very strong ferromagnetic exchange of the order of 200 cm(-1) in an endohedral radical hetero-metallo-fullerene molecule Gd2@C79N. Calculations performed on the anisotropic Dy2@C79N molecule reveal that very strong Dy-radical exchange not only quenches the QTM effects but also immensely enhances the barrier height for magnetization reversal.